THE USE OF AUDIOVISUAL MEDIA TO IMPROVE THE SPEECH SKILLS OF PRIVATE SCHOOL STUDENTS - Friska Hadi Septiarini (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to improve speaking skills through the use of audiovisual media in class IB SD Negeri Suro, Kalibagor District. Speaking skills observed in this study include linguistic and non-linguistic aspects. In the linguistic aspect, it consists of stress, speech, vocabulary / diction, and sentence structure, while in the non-linguistic aspect it consists of fluency, disclosure of speech material, courage and attitude. This type of research is Classroom Action Research (CAR) which consists of 2 cycles. The subjects of this study were 22 students of SD Negeri Suro class IB. The research design used includes the planning, implementation, observation, and reflection stages. The data collection instruments used were performance tests, teacher and student observation sheets and documentation. The data analysis technique used is descriptive quantitative data analysis. This study shows that the use of audiovisual media can improve the speaking skills of grade IB SD Negeri Suro students in terms of process and outcome. The process improvement is seen from the average results of student activity observations which are included in the good category in the first cycle with a percentage of 45.5% increasing in the second cycle to 68% and are included in the very good category. In terms of results, it is evidenced by the average value of students' speaking skills in pre-action 67.54 increased to 73.05 in cycle I and increased to 75.64 in cycle II. This shows that students' speaking skills increased from cycle I to cycle II.